Development Committee Closing Press Conference - Belka, Marek; Kim, Jim Yong; Lagarde, Christine (2016)
Marek Belka, Chairman of the Development Committee, stated that there was a very broad, uniform support for the twin goals of the World Bank Group. He noted the resounding support for internal reforms at the World Bank Group. Jim Yong Kim, President of the World Bank Group, spoke about the change process and the success in developing and bringing together Global Practices and cross-cutting solution areas throughout the world. He noted the IDA replenishment and new financial arrangements that will allow increased lending in the next few years. He concludes by noting the need for a carbon price and the need to reduce fossil fuel subsidies, the importance of energy efficiency and improved performance standards, and and also long-term finance for renewable energy. Christine Lagarde, IMF Managing Director, affirms that the IMF will continue to work on the issues of inequality, gender inclusion, growth, and the job market, and the fiscal aspect of climate change and how those matters of macroeconomic criticality can be addressed using fiscal tools. They fielded questions on IMF governance reform, the impact of technological change on employment, and the pace of the Global Infrastructure Facility.